Evaluation of bitumen modified properties by adding up carbide lime as an addictive material - Tan, Kok Chuan (Universiti Malaysia Sarawak, UNIMAS, 2010)
This thesis presents the design and implementation of solar photovoltaic (PV) system with a sun tracker. PVs are arrays of cells containing a solar photovoltaic material that convert radiation into direct current electricity via photovoltaic effects. Installation of a sun tracker is one of the approaches to improve the performance of a solar photovoltaic system. A sun tracker is a device for orientating photovoltaic panel towards the sun. The aim of this paper is to examine the performance of a solar photovoltaic system with a sun tracker in Batu Lintang, Kuching, Sarawak (1º32’09.73’’N, 110º20’32.70E). A designed and developed solar photovoltaic system that is equipped with a sun tracker is presented. The developed system consists of five modules, i.e., a sensor system, a linear actuator system, a tracking mechanism, a battery storage system and charge controller, and a microcontroller system. Besides, the performance of the photovoltaic system with sun tracker and without sun tracker are compared, analyzed and evaluated with experiments. Concluding remarks is further presented.